Analisis Kinerja Mesin CNC Milling 3 Axis pada Pembuatan Pipa Jet Oil - Trisanti, Trisanti; Susanto, Dian; Atmadja, Ifan Haristian (FAKULTAS TEKNIK UNIVERSITAS SUBANG, 2024)
The study evaluated the performance of a 3-axis CNC milling machine in the production of jet oil pipes with a focus on achieving a high level of precision. Through variation of cutting parameters and feeding speed, the machine succeeded in reaching the industry standard for jet oil pipe production. Optimization of parameters improved production efficiency, demonstrated by results that achieved the desired precision tolerance. Cutting tool wear analysis provides insight into machine performance and possible repair actions. This research confirms the potential of 3 axis CNC milling machines in addressing the challenge of high-precision jet oil pipe production, contributing to the development of CNC Milling technology in the context of the oil and gas industry.